Classical rhetoric for the modern student - Corbett, Edward P.J (Oxford University Press, 1999)
Widely used in advanced composition and writing courses, Classical Rhetoric for the Modern Student discusses the three vital components of classical rhetoric--argument, arrangement, and style--bringing these elements to life and demonstrating their effective use in yesterday's and today's writing. Presenting its subject in five parts, the text provides grounding in the elements and applications of classical rhetoric; the strategies and tactics of argumentation; the effective presentation and organization of discourses; the development of power, grace, and felicity in expression; and the history of rhetorical principles. Numerous examples of classic and contemporary rhetoric, from paragraphs to complete essays, appear throughout the book, many followed by detailed analyses.